Sub-kiloparsec empirical relations and excitation conditions of HCN and HCO+ J = 3-2 in nearby star-forming galaxies - García-Rodríguez, Axel; Usero, A.; Leroy, A. K.; Bigiel, F.; Jiménez-Donaire, M. J.; Liu, D.; Querejeta, M.; Saito, T.; Schinnerer, E.; Barnes, A.; Belfiore, F.; Bešlić, I.; et al. (Astronomy and astrophysics, 2023)
We present new HCN and HCO+ (J = 3–2) images of the nearby star-forming galaxies (SFGs) NGC 3351, NGC 3627, and NGC 4321. The observations, obtained with the Morita ALMA Compact Array, have a spatial resolution of ∼290–440 pc and resolve the inner Rgal ≲ 0.6–1 kpc of the targets, as well as the southern bar end of NGC 3627. We complement this data set with publicly available images of lower excitation lines of HCN, HCO+, and CO and analyse the behaviour of a representative set of line ratios: HCN(3–2)/HCN(1–0), HCN(3–2)/HCO+(3–2), HCN(1–0)/CO(2–1), and HCN(3–2)/CO(2–1). Most of these ratios peak at the galaxy centres and decrease outwards. We compare the HCN and HCO+ observations with a grid of one-phase, non-local thermodynamic equilibrium (non-LTE) radiative transfer models and find them compatible with models that predict subthermally excited and optically thick lines. We study the systematic variations of the line ratios across the targets as a function of the stellar surface density (Σstar), the intensity-weighted CO(2–1) (⟨ICO⟩), and the star formation rate surface density (ΣSFR). We find no apparent correlation with ΣSFR, but positive correlations with the other two parameters, which are stronger in the case of ⟨ICO⟩. The HCN/CO–⟨ICO⟩ relations show ≲0.3 dex galaxy-to-galaxy offsets, with HCN(3–2)/CO(2–1)–⟨ICO⟩ being ∼2 times steeper than HCN(1–0)/CO(2–1). In contrast, the HCN(3–2)/HCN(1–0)–⟨ICO⟩ relation exhibits a tighter alignment between galaxies. We conclude that the overall behaviour of the line ratios cannot be ascribed to variations in a single excitation parameter (e.g., density or temperature).
Im Titel ist das Pluszeichen hochgestellt
Gesehen am 23.05.2023